2010
DOI: 10.1111/j.1540-6520.2011.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Tournaments to Reduce Agency Problems: The Case of Franchising

Abstract: Anecdotal evidence suggests that franchisors use multiunit franchising to reward franchisees. In this paper, we model multiunit franchising as the reward in a tournament-one solution to the franchising agency problem. We use a unique database of 68 restaurant franchisors and find support for the tournament model. Franchisors that seek franchisees with managerial experience and franchisors that build routines to share knowledge use more multiunit franchising. Also, franchisors that grow faster use more multiuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 72 publications
2
48
1
3
Order By: Relevance
“…In keeping with an appropriate recruitment, empirical evidence (outside franchising) shows that prior management experience may also be a strong factor in entrepreneurial success. Hence, franchisors interested in franchisee entrepreneurial traits may demand this experience to applicants (Gillis et al 2011). Furthermore, the requirement of prior experience may deter low-quality franchisees from misrepresenting their abilities when searching for rents (Shane 1998 Weaven et al (2010) found that the franchisees who did not appraise the franchise business concept accurately or had not objectively estimated their own capacity were more likely to take for granted unrealistic expectations of their performance.…”
Section: Franchisees' Prior Industry Experience Requirementsmentioning
confidence: 99%
“…In keeping with an appropriate recruitment, empirical evidence (outside franchising) shows that prior management experience may also be a strong factor in entrepreneurial success. Hence, franchisors interested in franchisee entrepreneurial traits may demand this experience to applicants (Gillis et al 2011). Furthermore, the requirement of prior experience may deter low-quality franchisees from misrepresenting their abilities when searching for rents (Shane 1998 Weaven et al (2010) found that the franchisees who did not appraise the franchise business concept accurately or had not objectively estimated their own capacity were more likely to take for granted unrealistic expectations of their performance.…”
Section: Franchisees' Prior Industry Experience Requirementsmentioning
confidence: 99%
“…which states franchising as part of a life cycle, where this system is adopted by firms to overcome scarce resources in their effort to growth, reverting in the future toward company ownership (Gillis et al, 2011). Oxenfeldt and Kelly were the first to formulate the termed resource scarcity view, which asserts that a nascent firm builds a brand in order to create economies of scale in advertising and purchasing (J. G. Combs et al, 2010;Oxenfeldt & Kelly, 1969).…”
Section: Resource Acquisition Theorymentioning
confidence: 99%
“…These issues are investigated on the lenses of many perspectives, but five of them are the most prevalent (Dant et al, 2011) -resource acquisition theory (Oxenfeldt & Kelly, 1969), agency theory (Fama & Jensen, 1983a, 1983b, transaction cost analysis (WILLIAMSON, 1985), signaling Theory (Gallini & Lutz, 1992;Gallini & Wright, 1990) and property rights theory (Demsetz, 1966;Hart & Moore, 1990;Maness, 1996) -although scholars have been using many other theoretical perspective approaches as well -stakeholder theory (D. Altinay & Miles, 2006), tournament theory (James G. Combs, Ketchen Jr, & Short, 2011;Gillis, McEwan, Crook, & Michael, 2011) , institutional theory (D. Altinay & Miles, 2006), RBV (Barthélemy, 2008;Fladmoe-Lindquist, 1996), upper echelons theory (J. G. , learning theory (J. G. Combs, Ketchen, Shook, & Short, 2010); plural theory (Dant & Kaufmann, 2003), risk-sharing theory (Hsu, Jang, & Canter, 2010), social exchange theory (James G. Combs et al, 2011), resource dependence theory (Dant & Gundlach, 1999), among other perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Tournaments have been used to explain many structures, from the obvious application to sporting tournaments (e.g. Bothner, Kang & Stuart 2007) to situations as diverse as innovation contests (Boudreau, Lacetera & Lakhani 2011), competition between broilerchicken farmers to gain sales to large buyers (Knoeber & Thurman 1994), multiunit franchising (Gillis et al 2011) and many others.…”
Section: Support For Large Pay Gaps: Tournament Theorymentioning
confidence: 99%